Valores romanos y ejes transversales - García de Paso Carrasco, María Dolores; Arcos Pereira, Trinidad (1999)
The paper deals with the values of Roman society which had an influence on the future. This values are individual and social. Humanitas is presented as a summary of values. This is referred to the didactic of Classical Culture in secondary schools.
Keywords: Humanismo; Romanos